Big hungry bear (The) : the little mouse, the red ripe strawberry, and - Wood, Don and Audrey (New York : Scholastic Inc, 1984)
The little mouse will do anything to save his strawberry from the big, hungry bear.
Keywords: Mice--Fiction; Children stories